CSF-Neurofilament Light Chain Levels in NMDAR and LGI1 Encephalitis: A National Cohort Study - Nissen, Mette Scheller; Ryding, Matias; Nilsson, Anna Christine; Madsen, Jonna Skov; Olsen, Dorte Aalund; Halekoh, Ulrich; Lydolph, Magnus; Illes, Zsolt; Blaabjerg, Morten (Frontiers in Immunology, 2021)
Background and Objectives: The two most common autoimmune encephalitides (AE), N-methyl-D-Aspartate receptor (NMDAR) and Leucine-rich Glioma-Inactivated 1 (LGI1) encephalitis, have been known for more than a decade. Nevertheless, no well-established biomarkers to guide treatment or estimate prognosis exist. Neurofilament light chain (NfL) has become an unspecific screening marker of axonal damage in CNS diseases, and has proven useful as a diagnostic and disease activity marker in neuroinflammatory diseases. Only limited reports on NfL in AE exist. We investigated NfL levels at diagnosis and follow-up in NMDAR and LGI1-AE patients, and evaluated the utility of CSF-NfL as a biomarker in AE. Methods: Patients were included from the National Danish AE cohort (2009-present) and diagnosed based upon autoantibody positivity and diagnostic consensus criteria. CSF-NfL was analyzed by single molecule array technology. Clinical and diagnostic information was retrospectively evaluated and related to NfL levels at baseline and follow-up. NMDAR-AE patients were subdivided into: primary (idiopathic or teratoma) or secondary NMDAR-AE (post-viral or concomitant with malignancies/demyelinating disease). Results: A total of 74 CSF samples from 53 AE patients (37 NMDAR and 16 LGI1 positive) were included in the study. Longitudinal CSF-NfL levels was measured in 21 patients. Median follow-up time was 23.8 and 43.9 months for NMDAR and LGI1-AE respectively. Major findings of this study are: i) CSF-NfL levels were higher in LGI1-AE than in primary NMDAR-AE at diagnosis; ii) CSF-NfL levels in NMDAR-AE patients distinguished idiopathic and teratoma cases from cases with other underlying etiologies (post-herpes simplex or malignancies/demyelinating diseases) and iii) Elevated CSF-NfL at diagnosis seems to be associated with worse long-term disease outcomes in both NMDAR and LGI1-AE. Discussion: CSF-NfL measurement may be beneficial as a prognostic biomarker in NMDAR and LGI1-AE, and high CSF-NfL may foster search for underlying etiologies in NMDAR-AE. Further studies on larger cohorts, using standardized methods, are warranted.